Cooperation or Confrontation? Analyzing the Existing Policy Provisions, Intergovernmental Mechanisms, and Practical Challenges of Cooperative Federalism in Nepal - Bhul, Baburam (Indonesian Association for Public Administration, 2025)
This study examines the policy and practice of cooperative federalism in Nepal by analyzing constitutional mandates, legislative frameworks, and empirical evidence. The principles of cooperation, coexistence, and coordination established in the Constitution of Nepal serve as a foundation for institutionalizing cooperative federalism, with the caveat that political, fiscal, and administrative factors have challenged its effective implementation. Although decentralization processes have been initiated, political parties appear unwilling to devolve power, mostly considering centralization as a means of control rather than fostering intergovernmental collaboration. Furthermore, fiscal challenges, jurisdictional ambiguities, and weak institutional mechanisms impede effective federal governance. The findings show that legal ambiguities, political centralization, restricted financial independence, and the ineffectiveness of coordinating mechanisms have led to tenacious difficulties in cooperative governance, resulting in inefficiencies and conflicts among all tiers of government that undermine policy coherence and service delivery. This study demands a clearer devolution of powers, fiscal autonomy, institutionalized intergovernmental coordination, and a reduction in political interference to strengthen cooperative federalism. This approach eventually subsidizes a more resilient and sustainable governance agenda that aligns with constitutional principles of inclusive governance.